This study aims to analyze the influence of the Suronan tradition on improving the social spirituality of the community in Ngawonggo Village, Malang Regency, East Java. The primary focus is to understand how cultural and religious rituals performed during the 1 Suro observance interact with the community’s spiritual dispositions, as interpreted through the concepts of communitas and moral habitus within symbolic anthropology. This research employs a qualitative methodology, utilizing participato - Faturahman, Muhamad; Izra Berakon (Penamas, 2025)
This study aims to analyze the influence of the Suronan tradition on improving the social spirituality of the community in Ngawonggo Village, Malang Regency, East Java. The primary focus is to understand how cultural and religious rituals performed during the 1 Suro observance interact with the community’s spiritual dispositions, as interpreted through the concepts of communitas and moral habitus within symbolic anthropology. This research employs a qualitative methodology, utilizing participatory observation, in-depth interviews, and documentation to explore the symbolic significance, spiritual importance, and social functions of the Suronan tradition. The findings indicate that the observance of Suronan not only serves as an annual ritual but also enhances social cohesion, deepens spiritual consciousness, and provides an opportunity for reflection on values of unity and life. Suronan functions as a medium through which social and spiritual meanings are reproduced and negotiated, thereby contributing to the development of a more robust social spirituality. Consequently, this study concludes that the Suronan tradition plays a strategic role in fostering social harmony while strengthening the spiritual identity of the residents of Ngawonggo Village.